DOES COVID-19 EXACERBATE POVERTY RATE IN INDONESIA? - Birgitta Dian Saraswati; Fajar Setiawan; Virgiana Nugransih Siwi (Jurnal Ekonomi dan Pendidikan, 2022)
Poverty is still the focus of the Indonesian government. The Covid-19 pandemic has the potential to increase the number of poor people. Therefore, this study aims to examine the effect of the COVID-19 pandemic and macroeconomic factors of inflation, economic growth and unemployment on poverty in 34 provinces in Indonesia. Using the Random Effect Model, we find that unemployment significantly affects poverty in Indonesia. while inflation and economic growth have no significant effect on poverty. In addition, this study proves that the provinces of Java and Bali, which are the areas with the highest number of Covid-19 exposures in Indonesia, have a higher poverty rate than other provinces. Therefore, vaccination is the right policy so that people can carry out normal activities and economic activities will resume running and people's incomes can incre